The Effect of Dosage and Frequency of Leri Water Spraying on Phalaenopsis Fuller's Pink Stripe Orchid Growth of Aclimatisation - Sri Hartati; Ongko Cahyono (Pusat Penelitian dan Pengembangan Bioteknologi dan Biodiversitas (P3BB) LPPM UNS, 2022)
The phalaenopsis hybrid has become an economically important flower in the horticultural sector. Phalaenopsis Fuller's Pink Stripe Orchid is a hybrid orchid resulting from a cross between Phalaenopsis Fuller's Pink Swallow and Phalaenopsis Fullers Black Stripe. Rice washing water (leri) is a residue that accumulates when washing rice. This residue is usually thrown away when it is actually rich in various organic and mineral compounds. Waste that is wasted in vain can be used as nutrients for the growth of orchid plants. This research was conducted to study the effect of dose and frequency of leri water spraying on the growth of Phalaenopsis Fuller's Pink Stripe orchid at the vegetative stage. This study consisted of 10 treatments, namely giving 5 ml of water every 2 days (L1), 10 ml every 2 days (L2), 15 ml every 2 days (L3), 5 ml every 4 days (L4). a dose of 10 ml every 4 days (L5), a dose of 15 ml every 4 days (L6), a dose of 5 ml every 6 days (L7), a dose of 10 ml every 6 days (L8), a dose of 15 ml every 6 days (L9), and control treatment (L0). Each treatment was repeated 3 times. Based on the results of the study, it are often all over that there's no important interaction between the dose and also the frequency of administration of Leri water on the growth and performance of the Phalaenopsis Fuller's Pink Stripe.Keywords: Rice Wash Water, Phalaenopsis Fuller's Pink Stripe, vegetative growth